Tissue ablation with multi-millimeter depth and cellular-scale collateral damage by a femtosecond mid-infrared laser tuned to the amide-I vibration - Tian, Kan (2024)
Laser ablation of bio-tissues is the key technology of future surgeries, owing to the merits of submicron accuracy, non-contact operation, and precision control assisted by automation and computer intelligence. Excellent efficiency, minimal collateral damage, biological safety, and tissue selectivity are the ideal parameters for delicate surgical applications. Here, by exploring the mid-infrared (MIR) resonant ablation and the femtosecond cold processing, tissue ablation with multi-millimeter depth and cellular collateral damage, enabled by a tabletop femtosecond MIR optical parametric amplifier operating at the amide-I resonant wavelength of 6.1 µm, is demonstrated. Remarkably, the collateral damage is observed to be 15, <4, and <1 µm in the porcine cornea, sclera, and articular cartilage, respectively, with multi-millimeter incision depth. In addition, preliminary proof-of-concept experiments of tissue-selective ablation, microchannels on cartilage for drug delivery, laser glaucoma, keratotomy, neurologic tissue incision, dentin deep crater formation, and hypertrophic scarring ablation are demonstrated, which pave the way for high-precision surgical applications with a tabletop solution.